Simulation investigation of Ku band gridless reltron - Tripathi P.; Kumar A.; Dwivedi S.; Jain P.K. (My University, 2025)
In this paper, the performance of highly efficient Gridless-reltron in Ku band with multiple extraction cavities is investigated. CST particle in cell (PIC) code is used to model the High power microwave (HPM) source, Gridless-reltron. The RF interaction structure used in gridless reltron is a side-coupled cavity which is comprised of the main cavity and coupled cavity. The coupled cavity is radially mounted on the top of the main cavity and by inserting a metal disc at the centre of the main cavity the main cavity is divided into two equal parts namely front main cavity and back main cavity. This RF interaction structure resonates at three modes namely 0-mode, π/2 mode and π-mode. Out of these three modes only π/2-mode is desired mode because it is only unstable mode and it grows in amplitude. Simulation results predict that the device is resonating at a center frequency of 15.314 GHz with typical output parameters-microwave power of 6 MW, pulse width of 1 μsec and efficiency of ~24%, when supplied with the total tube voltage of 250 kV, beam current of 100 A, and a relatively low focusing magnetic field of 0.48 T. © 2018 IEEE.